Model‐assisted process characterization and validation for a continuous two‐column protein A capture process. Issue 1 (6th November 2018) - Baur, Daniel; Angelo, James; Chollangi, Srinivas; Müller‐Späth, Thomas; Xu, Xuankuo; Ghose, Sanchayita; Li, Zheng Jian; Morbidelli, Massimo
Abstract: In this study we introduce three process characterization approaches toward validation of continuous twin‐column capture chromatography (CaptureSMB), referred to as "standard, " "model assisted, " and "hybrid." They are all based on a traditional risk‐based approach, using process description, risk analysis, design‐of‐experiments (DoE), and statistical analysis as essential elements. The first approach, the "standard" approach uses a traditional experimental DoE to explore the design space of the high‐ranked process parameters for the continuous process. Due to the larger number of process parameters in the continuous process, the DoE is extensive and includes a larger number of experiments than an equivalent DoE of a single column batch capture process. In the investigated case, many of the operating conditions were practically infeasible, indicating that the design space boundaries had been chosen inappropriately. To reduce experimental burden and at the same time enhance process understanding, an alternative "model assisted" approach was developed in parallel, employing a chromatographic process model to substitute experimental runs by computer simulations. Using the "model assisted" approach only experimental conditions that were feasible in terms of process yield constraints (>90%) were considered for statistical analysis. The "model assisted" approach included an optimization part that identified potential boundaries of the design space automatically. In summary, the "model assisted" approach contributed to increased process understanding compared to the "standard" approach. In this study, a "hybrid" approach was also used containing the general concepts of the "standard" approach but substituting a number of its experiments by computer simulations. The presented approaches contain essential elements of the Food and Drug Administration's process validation guideline. Abstract : In this study we introduce three process characterization approaches toward validation of continuous twin‐column capture chromatography (CaptureSMB), referred to as "standard, " "model assisted, " and "hybrid." They are all based on a traditional risk‐based approach, using process description, risk analysis, design‐of‐experiments (DoE), and statistical analysis as essential elements.